Pastoral Konseling sebagai Kebutuhan Pendampingan Kepada Jemaat Lanjut Usia - Woindah Mezak (PT. Giat Konseling Nusantara, 2024)
There are many factors behind the importance of pastoral assistance services for elderly parents. Among them is accompaniment to be able to provide spiritual services, give meaning to life and enable the elderly to overcome any problems and struggles they face. And what is most important here is how the church, in this case the pastors and congregational councils, can build the basis of assistance services for the elderly. This research is motivated by the fact that Church of GMIST LIUNKENDAGE held intense communication with several elderly parents who did not receive attention in pastoral care,so that you feel cared for,This research uses qualitative methods and a descriptive approach. Data is collected by interview techniques. Qualitative analysis is taken from data interpretation by providing information and research.